2020
DOI: 10.1186/s12903-020-01194-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of zinc sulfate mucoadhesive formulation on recurrent aphthous stomatitis: a randomized double-blind, placebo-controlled clinical trial

Abstract: Background: Recurrent aphthous stomatitis (RAS) is a common lesion that affects the oral mucosa. There are several methods to treat RAS, including systemic and topical formulations. This study was conducted to evaluate the anti-inflammatory effect of topical zinc sulfate and its efficacy in the treatment of RAS. Methods: A double-blind randomized clinical trial was conducted on 46 patients with RAS. They were randomly assigned into two groups to receive a zinc sulfate mucoadhesive tablet or placebo for 7 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Zinc sulfate has also been shown to treat RAS. One double‐blind randomized control trial (RCT) of 46 patients with RAS found a significant reduction in the diameter of lesions after 3, 5, and 7 days of the study and significant reduction in pain starting the fourth day of the study when treated with a zinc sulfate mucoadhesive tablet for 7 days compared to placebo 15 …”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc sulfate has also been shown to treat RAS. One double‐blind randomized control trial (RCT) of 46 patients with RAS found a significant reduction in the diameter of lesions after 3, 5, and 7 days of the study and significant reduction in pain starting the fourth day of the study when treated with a zinc sulfate mucoadhesive tablet for 7 days compared to placebo 15 …”
Section: Preventionmentioning
confidence: 99%
“…One double-blind randomized control trial (RCT) of 46 patients with RAS found a significant reduction in the diameter of lesions after 3, 5, and 7 days of the study and significant reduction in pain starting the fourth day of the study when treated with a zinc sulfate mucoadhesive tablet for 7 days compared to placebo. 15 Vitamin D deficiency also seems to be associated with RAS. A systematic review and meta-analysis of five case-control, pooled studies reported statistically significant lower levels of vitamin D in RAS patients.…”
Section: Dietary Deficienciesmentioning
confidence: 99%
“…In the study of Anahita Ghorbani et al mucoadhesive tablets were prepared which contained carbopol 940, sodium alginate, zinc sulfate and starch. Results showed clinically and statistically the effectiveness of zinc mucoadhesive tablets as a topical drug delivery system, on decreasing pain, the diameter of the wound, and length of the recovery period of recurrent aphthous stomatitis compared to the control group (108). Another study by Perioli et al sustained-release mucoadhesive bilayered tablets were designed by mixing mucoadhesive polymers and an inorganic matrix (hydrotalcite) to apply flurbiprofen in oral cavity.…”
Section: Anti-inflammatory Drugsmentioning
confidence: 98%
“…Data from 36 RCTs [20,22,24,26,[28][29][30][40][41][42]47,48,50,53,54,[63][64][65]70,71,[75][76][77]80,82,83,[85][86][87][88][89][92][93][94][95][96] with 32 pairwise comparisons among 22 interventions were pooled. In terms of possible adverse events, triamcinolone performed better, with none occurring in 259 subjects, compared to amlexanox, chitosan, dexamethasone, doxycycline, penicillin and placebo.…”
Section: Adverse Effectmentioning
confidence: 99%